Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s11664-004-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on Cu particles-enhanced SnPb composite solder

Abstract: The Sn-Pb solder is widely used in the electronics industry. With the development of surface mount technology and miniaturization of elements, mechanical properties of the solder are critical. Creep resistance and size stability of soldered joints are important for optical electronics. In the present work, Cu particles with a size of about 8 µm were added to the eutectic 63Sn-37Pb solder to improve the creep property of the soldering alloy. The contents of the Cu particles are 5 vol.% and 10 vol.% separately. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This can be attributed to the presence of relatively harder second phase that serves as crack nucleation sites, resulting in a decrease in FS under tensile loading condition. This observation is consistent with the findings of other researchers working in other solder materials [7,10,38,42,[45][46][47].…”
Section: Mechanical Characteristicssupporting
confidence: 93%
“…This can be attributed to the presence of relatively harder second phase that serves as crack nucleation sites, resulting in a decrease in FS under tensile loading condition. This observation is consistent with the findings of other researchers working in other solder materials [7,10,38,42,[45][46][47].…”
Section: Mechanical Characteristicssupporting
confidence: 93%
“…per cent) in the bulk of the solder joints with 100, 50, 20 and 10 μ m SOH, respectively. Yan et al (2004) studied the effect of Cu on the tensile strength of SnPb solder, and they found that adding Cu made the grain size of the solder refined and enhanced the tensile strength. Accordingly, it can be inferred that the increase of Cu concentration in the solder bulk would improve the mechanical properties of the solder bulk through solid solution and refined grains.…”
Section: Resultsmentioning
confidence: 99%
“…Red copper and pure aluminum are widely used in the power, electronics, refrigeration, and other industries because of their excellent electrical conductivity, thermal conductivity, plasticity, corrosion resistance, and ease of processing. [1][2][3] However, due to the high price of copper, replacing aluminum with pure aluminum is an effective way to reduce costs. In fact, most current applications where aluminum is used to substitute copper adopt the strategy of reducing the amount of copper used in products while using aluminum as a substitute to fully utilize the advantages of copper-aluminum composites.…”
Section: Introductionmentioning
confidence: 99%